RESOURCE-SAVING TECHNOLOGY FOR REDUCING SILK THREAD WINDING DEFECTIVENESS ON TWISTING MACHINES - G. N. Valiyev, J. I.Oripov (International Journal of Literature and Language Studies, 2026)
The analysis of the quality of winding on twisting machines has been carried out, the reasons for the formation and ways of eliminating winding defects and reducing the waste of raw materials during the processing of crepe yarns of natural silk have been established. Developed resource-saving technology for reducing silk thread winding defectiveness on twisting machines.